Transitional housing in forensic mental health: considering consumer lived experience - Clark Patrick Heard; Jared Scott; Allan Tetzlaff; Heather Lumley (BMC, 2019)
Abstract Background For individuals involved in the forensic mental health system, access to transitional housing can offer a bridge between custody and independence. Using a methodology consistent with interpretative phenomenological analysis (IPA), this study considers the meaning associated with such participation. In this Canadian study, data was collected via interview with six individuals (n = 6) who resided, for a minimum six (6) months, in justice focused transitional housing that involved a partnership between a rural forensic mental health care facility and a nearby urban transitional housing provider. Results Following each participant interview, data was transcribed verbatim and coded for themes. Multiple methods were employed to support trustworthiness. Results indicate that participation enabled enhanced social participation, self-esteem/efficacy, community integration and renewal of daily living skills. Participants identified that involvement in justice focused transitional housing enabled development of community living skills, cultivated self-confidence and enhanced personal resilience in their transition from a secure forensic mental health facility to more independent community tenure. Conclusions Participants in this research clearly identified the importance of transitional housing programs in supporting their move from a forensic mental health facility to the community. Not all forensic involved individuals will need this type or level of support to support their transition. Practically, however, the nature of forensic hospitalization can present real challenges for occupational participation and maintenance of community living skills. Transitional housing, accountable to unique forensic mental health and justice inputs, can offer a valuable bridge to the community.